Low-melting-point welding brazing filler metal and preparation method thereof
Through multiple smelting heat treatment and high-pressure sintering technology, welding solder materials including Zn, Mn, Hf and Sn were prepared, which solved the problem of poor wetting and insufficient corrosion resistance on the copper surface of Sn-Zn solder materials, achieved high wetting and corrosion resistance of welding solder materials, and improved welding quality and joint stability.
Patent Information
- Application Number
- CN202510289136.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-12
- Publication Date
- 2025-04-08
- Estimated Expiration
- 2045-03-12
AI Technical Summary
Sn-Zn solder has poor wettability on the copper surface and Zn elements are prone to oxidation, resulting in unstable welding quality and poor corrosion resistance, which limits its further development and widespread application.
By performing multiple melting heat treatments in an inert gas protection environment, the intermediate is prepared and sintered with Bi particles at high pressure to form a welding solder material containing Zn, Mn, Hf and Sn, thereby improving its wettability and corrosion resistance.
It significantly improves the wetting and corrosion resistance of welding brazing, enhances the firmness and service life of welding joints, and adapts to traditional welding process parameters.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of welding materials, and in particular relates to a low melting point welding brazing filler metal and a preparation method thereof. Background Art
[0002] Among the various types of lead-free solders, Sn-Zn solders have gradually emerged with their significant advantages and have become a potential competitor in the field of lead-free solders. They are relatively low-cost, effectively reducing production inputs, and meeting the cost control needs of large-scale industrial applications; their melting point is very close to that of traditional Sn-Pb solders, and in practical applications, there is no need to make major adjustments to existing welding processes and equipment, greatly reducing the cost of process changes and technical difficulties; at the same time, Sn-Zn solders also have excellent mechanical properties and can meet the requirements for welding strength and stability under various complex working conditions.
[0003] However, Sn-Zn solder also has obvious shortcomings. It has poor wettability with the copper surface, which makes it difficult to spread evenly on the copper surface during welding, seriously affecting the firmness and quality stability of welding; Zn element is chemically active and easily oxidized, resulting in reduced solder performance; and Sn-Zn solder has poor corrosion resistance and is easily corroded in complex working environments, greatly shortening the service life of the welded joint. These shortcomings are like insurmountable obstacles, which seriously restrict the further development and widespread application of Sn-Zn lead-free solder.
[0004] Therefore, providing a welding brazing material with good corrosion resistance and low melting point is an important problem to be solved in the art. Summary of the invention
[0005] In order to solve the problems existing in the prior art, the present invention provides a low melting point solder and a preparation method thereof. Specifically, the technical solution of the present invention includes the following contents: A method for preparing a low melting point solder, the method comprising the following steps: Sn particles and Zn particles are subjected to a first smelting heat treatment in an inert gas protective environment and then cooled to obtain intermediate 1, Sn particles and Mn particles are subjected to a second smelting heat treatment in an inert gas protective environment and then cooled to obtain intermediate 2, Sn particles and Hf particles are subjected to a third smelting heat treatment in an inert gas protective environment and then cooled to obtain intermediate 3, intermediate 1, intermediate 2, intermediate 3 and Bi particles are mixed by ball milling, and then sintered under high pressure and quenched to release the pressure to obtain the welding brazing material.
[0006] Furthermore, the purity of the Zn particles is 99.9%.
[0007] Furthermore, the purity of the Sn particles is 99.99%.
[0008] Furthermore, the inert gas includes nitrogen or argon.
[0009] Furthermore, the smelting temperature of the first smelting is 450-550° C., and the smelting time is 30-60 min.
[0010] Furthermore, the smelting temperature of the second smelting is 1300-1500° C., and the smelting time is 40-60 min.
[0011] Furthermore, the smelting temperature of the third smelting is 2300-2500° C., and the smelting time is 80-100 min.
[0012] Furthermore, the ball milling environment is an argon or nitrogen protective environment.
[0013] Furthermore, the ball-to-material ratio of the ball mill is 10:1-2.
[0014] Furthermore, the rotation speed of the ball mill is 100-200 r / min. Furthermore, the ball milling time is 8 to 10 hours.
[0015] Furthermore, the high pressure sintering temperature is 900-1200°C.
[0016] Furthermore, the pressure of the high pressure sintering is 3~4GPa.
[0017] Furthermore, the high pressure sintering time is 45 to 70 minutes.
[0018] Furthermore, the solder comprises the following components by weight percentage: 9.0% of Zn particles, 2.5-3.5% of Mn particles, 1.8-2.6% of Bi particles, 0.01-0.5% of Hf particles and the remainder of Sn particles.
[0019] Compared with the prior art, the present invention has the following beneficial effects: (1) In the present invention, Bi can effectively reduce the melting point of the solder and improve the wettability of the solder; the addition of Hf has a significant effect on improving the corrosion resistance of the solder. On the one hand, Hf can enhance the stability of Zn and effectively reduce the dissolution rate of Zn in the corrosive medium; on the other hand, the addition of Hf increases the content of the oxide film and enhances the stability of the oxide film, thereby improving the stability of the solder and thus enhancing the corrosion resistance of the solder; Mn can effectively reduce the surface tension of the solder, while Hf can refine the grains and homogenize the microstructure. Under the synergistic effect of the two, the solder can be spread more quickly and evenly on the surface of the base material, thereby improving the welding quality; the present invention ingeniously integrates the three elements of Bi, Mn and Hf into the solder with a low melting point. These three elements cooperate with each other, complement each other, and work together to improve the wettability and corrosion resistance of the solder with a low melting point, making the welding joint more firm and reliable, and significantly improving the welding quality.
[0020] (2) The preparation method provided by the present invention has an exquisite process design. In the preparation process, Zn, Mn, and Hf are first placed in a high-temperature environment to react with Sn respectively, thereby obtaining intermediates 1, 2, and 3. This step promotes the full fusion of the elements and lays the foundation for subsequent performance improvement; then the intermediates 1, 2, and 3 are subjected to high-pressure sintering with Bi. In the high-pressure environment, the substances are in close contact, and the atoms diffuse and recombine with each other, making the structure of the prepared welding brazing material more compact, greatly reducing internal defects, and enhancing the intermolecular force, thereby further enhancing its corrosion resistance. DETAILED DESCRIPTION
[0021] The technical solution of the present invention will be clearly and completely described below through the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative work are within the scope of protection of the present invention.
[0022] Unless otherwise specified, the raw materials and reagents used in the present invention are commercially available or can be prepared by known methods.
[0023] Example 1: A low melting point solder comprises the following components by weight percentage: 9.0% Zn, 3.5% Mn, 1.8% Bi, 0.01% Hf and the balance Sn. The specific preparation method comprises the following steps: Weigh Sn particles with a purity of 99.99% and Zn particles with a purity of 99.9% according to a certain weight percentage and put them into a quartz tube. Reduce the vacuum degree in the quartz tube to 3×10 -2Pa, nitrogen was filled in until the pressure reached 0.1 MPa, and the first smelting heat treatment was carried out at 450 °C in a nitrogen protection environment for 30 min and then cooled to obtain the intermediate 1; Sn particles and Mn particles with a purity of 99.99% were weighed according to a certain weight percentage and put into a quartz tube, and the vacuum degree in the quartz tube was reduced to 3×10 -2 Pa, nitrogen was filled in until the pressure reached 0.1 MPa, and the second smelting heat treatment was carried out at 1300 °C in a nitrogen protection environment for 40 min and then cooled to obtain the intermediate 2; Sn particles and Hf particles with a purity of 99.99% were weighed according to a certain weight percentage and put into a quartz tube, and the vacuum degree in the quartz tube was reduced to 3×10 -2 Pa, nitrogen was filled in until the pressure reached 0.1MPa, and the third smelting heat treatment was carried out at a temperature of 2300°C for 60min in a nitrogen protective environment, and then cooled to obtain intermediate 3; in a nitrogen protective environment, intermediate 1, intermediate 2, intermediate 3 and Bi particles were mixed at a ball-to-material ratio of 10:1 and a speed of 100r / min for 8h to obtain a mixture, and the mixture was press-molded in a mold at a pressure of 400MPa by a tablet press to obtain a green sheet, and the temperature was increased at a heating rate of 100°C / min in a nitrogen protective environment. When the temperature reached 500°C, it was maintained at a pressure of 200MPa for 30min, and then the pressure was increased to 3GPa, and then the temperature was increased to 1000°C, and after keeping warm for 15min, it was quenched and unloaded to obtain the welding brazing filler metal.
[0024] Example 2: A low melting point solder comprises the following components by weight percentage: 9.0% Zn, 2.5% Mn, 2.2% Bi, 0.1% Hf and the balance Sn. The specific preparation method comprises the following steps: Weigh Sn particles with a purity of 99.99% and Zn particles with a purity of 99.9% according to a certain weight percentage and put them into a quartz tube. Reduce the vacuum degree in the quartz tube to 3.2×10 -2 Pa, argon was filled until the pressure reached 0.18 MPa, and the first smelting heat treatment was carried out at a temperature of 480 ° C for 40 min in an argon protection environment, and then cooled to obtain an intermediate 1; Sn particles and Mn particles with a purity of 99.99% were weighed according to a certain weight percentage and put into a quartz tube, and the vacuum degree in the quartz tube was reduced to 3.3×10 -2 Pa, argon was filled in until the pressure reached 0.17 MPa, and the second smelting heat treatment was carried out at a temperature of 1400 °C for 45 min in an argon protection environment, and then cooled to obtain the intermediate 2; Sn particles and Hf particles with a purity of 99.99% were weighed according to a certain weight percentage and put into a quartz tube, and the vacuum degree in the quartz tube was reduced to 3.4×10 -2Pa, argon was filled until the pressure reached 0.2MPa, and the third smelting heat treatment was carried out at a temperature of 2350℃ for 70min in an argon protective environment, and then cooled to obtain intermediate 3; in an argon protective environment, intermediate 1, intermediate 2, intermediate 3 and Bi particles were ball-milled and mixed at a speed of 120r / min for 9h at a ball-to-material ratio of 10:1.3, and the mixture was obtained. The mixture was press-molded in a mold at a pressure of 400MPa by a tablet press to obtain a green sheet, and the temperature was increased at a heating rate of 110℃ / min in an argon protective environment. When the temperature reached 500℃, it was maintained at a pressure of 220MPa for 40min, and then the pressure was increased to 3.2GPa, and then the temperature was increased to 1100℃, kept warm for 12min, and then quenched and unloaded to obtain the welding brazing filler metal.
[0025] Example 3: A low melting point solder comprises the following components by weight percentage: 9.0% Zn, 3.0% Mn, 2.2% Bi, 0.3% Hf and the balance Sn. The specific preparation method comprises the following steps: Weigh Sn particles with a purity of 99.99% and Zn particles with a purity of 99.9% according to a certain weight percentage and put them into a quartz tube. Reduce the vacuum degree in the quartz tube to 3.8×10 -2 Pa, argon was filled in until the pressure reached 0.25 MPa, and the first smelting heat treatment was carried out at a temperature of 520 ° C for 50 min in an argon protection environment, and then cooled to obtain an intermediate 1; Sn particles and Mn particles with a purity of 99.99% were weighed according to a certain weight percentage and put into a quartz tube, and the vacuum degree in the quartz tube was reduced to 3.7×10 -2 Pa, argon was filled in until the pressure reached 0.2 MPa, and the second smelting heat treatment was carried out at a temperature of 1450 ° C in an argon protection environment for 50 min and then cooled to obtain the intermediate 2; Sn particles and Hf particles with a purity of 99.99% were weighed according to a certain weight percentage and put into a quartz tube, and the vacuum degree in the quartz tube was reduced to 3.5×10 -2 Pa, argon was filled until the pressure reached 0.2MPa, and the third smelting heat treatment was carried out at a temperature of 2400℃ for 80min in an argon protective environment, and then cooled to obtain intermediate 3; in an argon protective environment, intermediate 1, intermediate 2, intermediate 3 and Bi particles were ball-milled and mixed at a speed of 180r / min for 9h at a ball-to-material ratio of 10:1.8 to obtain a mixture, and the mixture was press-molded in a mold at a pressure of 400MPa by a tablet press to obtain a pressed green sheet, and the temperature was increased at a heating rate of 100-120℃ / min in an argon protective environment. When the temperature reached 500℃, it was maintained at a pressure of 270MPa for 50min, and then the pressure was increased to 3.5GPa, and then the temperature was increased to 1200℃, and after keeping warm for 12min, it was quenched and unloaded to obtain a welding brazing filler metal.
[0026] Example 4: A low melting point solder comprises the following components by weight percentage: 9.0% Zn, 3.0% Mn, 2.6% Bi, 0.5% Hf and the balance Sn. The specific preparation method comprises the following steps: Weigh Sn particles with a purity of 99.99% and Zn particles with a purity of 99.9% according to a certain weight percentage and put them into a quartz tube. Reduce the vacuum degree in the quartz tube to 4×10 -2 Pa, nitrogen was filled in until the pressure reached 0.3 MPa, and the first smelting heat treatment was carried out at 550 ° C in a nitrogen protection environment for 60 min and then cooled to obtain the intermediate 1; Sn particles and Mn particles with a purity of 99.99% were weighed according to a certain weight percentage and put into a quartz tube, and the vacuum degree in the quartz tube was reduced to 4×10 -2 Pa, nitrogen was filled in until the pressure reached 0.3 MPa, and the second smelting heat treatment was carried out at 1500 °C in a nitrogen protection environment for 60 min and then cooled to obtain intermediate 2; Sn particles and Hf particles with a purity of 99.99% were weighed according to a certain weight percentage and put into a quartz tube, and the vacuum degree in the quartz tube was reduced to 4×10 -2 Pa, nitrogen was filled in until the pressure reached 0.3MPa, and the third smelting heat treatment was carried out at a temperature of 2500°C for 90min in a nitrogen protective environment, and then cooled to obtain intermediate 3; in a nitrogen protective environment, intermediate 1, intermediate 2, intermediate 3 and Bi particles were mixed at a ball-to-material ratio of 10:2 and a speed of 200r / min for 10h to obtain a mixture, and the mixture was press-molded in a mold at a pressure of 400MPa by a tablet press to obtain a green compact, and in a nitrogen protective environment, the temperature was increased at a heating rate of 120°C / min. When the temperature was raised to 500°C, it was maintained at a pressure of 300MPa for 60min, and then the pressure was increased to 4GPa, and then the temperature was increased to 1300°C, and after keeping warm for 10min, it was quenched and unloaded to obtain a welding brazing filler metal.
[0027] Comparative Example 1: A low melting point solder comprises the following components by weight percentage: 9.0% Zn, 2.6% Bi, 0.5% Hf and the balance Sn, and the specific preparation method comprises the following steps: Weigh Sn particles with a purity of 99.99% and Zn particles with a purity of 99.9% according to a certain weight percentage and put them into a quartz tube. Reduce the vacuum degree in the quartz tube to 4×10 -2 Pa, nitrogen was filled in until the pressure reached 0.3 MPa, and the first smelting heat treatment was carried out at 550 ° C for 60 min in a nitrogen protection environment, and then cooled to obtain the intermediate 1; Sn particles and Hf particles with a purity of 99.99% were weighed according to a certain weight percentage and put into a quartz tube, and the vacuum degree in the quartz tube was reduced to 4×10 -2Pa, nitrogen was filled in until the pressure reached 0.3MPa, and the third smelting heat treatment was carried out at a temperature of 2500°C for 90min in a nitrogen protective environment, and then cooled to obtain intermediate 3; in a nitrogen protective environment, intermediate 1, intermediate 3 and Bi particles were ball-milled and mixed at a speed of 200r / min for 10h in a ball-to-material ratio of 10:2 to obtain a mixture, and the mixture was press-molded in a mold at a pressure of 400MPa by a tablet press to obtain a green compact, and the temperature was increased at a heating rate of 120°C / min in a nitrogen protective environment. When the temperature was raised to 500°C, it was maintained at a pressure of 300MPa for 60min, and then the pressure was increased to 4GPa, and then the temperature was increased to 1300°C, and after keeping warm for 10min, it was quenched and unloaded to obtain the welding brazing filler metal.
[0028] Comparative Example 2: A low melting point solder comprises the following components by weight percentage: 9.0% Zn, 3.0% Mn, 0.5% Hf and the balance Sn, and the specific preparation method comprises the following steps: Weigh Sn particles with a purity of 99.99% and Zn particles with a purity of 99.9% according to a certain weight percentage and put them into a quartz tube. Reduce the vacuum degree in the quartz tube to 4×10 -2 Pa, nitrogen was filled in until the pressure reached 0.3 MPa, and the first smelting heat treatment was carried out at 550 ° C in a nitrogen protection environment for 60 min and then cooled to obtain the intermediate 1; Sn particles and Mn particles with a purity of 99.99% were weighed according to a certain weight percentage and put into a quartz tube, and the vacuum degree in the quartz tube was reduced to 4×10 -2 Pa, nitrogen was filled in until the pressure reached 0.3 MPa, and the second smelting heat treatment was carried out at 1500 °C in a nitrogen protection environment for 60 min and then cooled to obtain intermediate 2; Sn particles and Hf particles with a purity of 99.99% were weighed according to a certain weight percentage and put into a quartz tube, and the vacuum degree in the quartz tube was reduced to 4×10 -2 Pa, nitrogen was filled in until the pressure reached 0.3MPa, and the third smelting heat treatment was carried out at a temperature of 2500°C for 90min in a nitrogen protective environment, and then cooled to obtain intermediate 3; in a nitrogen protective environment, intermediate 1, intermediate 2 and intermediate 3 were mixed at a ball-to-material ratio of 10:2 and a speed of 200r / min for 10h to obtain a mixture, and the mixture was press-molded in a mold at a pressure of 400MPa by a tablet press to obtain a green sheet, and the temperature was increased at a heating rate of 120°C / min in a nitrogen protective environment. When the temperature reached 500°C, it was maintained at a pressure of 300MPa for 60min, and then the pressure was increased to 4GPa, and then the temperature was increased to 1300°C, and after keeping warm for 10min, it was quenched and unloaded to obtain the welding brazing filler metal.
[0029] Comparative Example 3: A low melting point solder comprises the following components by weight percentage: 9.0% Zn, 3.0% Mn, 2.6% Bi and the balance Sn, and the specific preparation method comprises the following steps: Weigh Sn particles with a purity of 99.99% and Zn particles with a purity of 99.9% according to a certain weight percentage and put them into a quartz tube. Reduce the vacuum degree in the quartz tube to 4×10 -2 Pa, nitrogen was filled in until the pressure reached 0.3 MPa, and the first smelting heat treatment was carried out at 550 ° C in a nitrogen protection environment for 60 min and then cooled to obtain the intermediate 1; Sn particles and Mn particles with a purity of 99.99% were weighed according to a certain weight percentage and put into a quartz tube, and the vacuum degree in the quartz tube was reduced to 4×10 -2 Pa, nitrogen was filled in until the pressure reached 0.3MPa, and the second smelting heat treatment was carried out at a temperature of 1500°C for 60min in a nitrogen protective environment, and then cooled to obtain intermediate 2; in a nitrogen protective environment, intermediate 1, intermediate 2 and Bi particles were mixed at a ball-to-material ratio of 10:2 and a speed of 200r / min for 10h to obtain a mixture, and the mixture was press-molded in a mold at a pressure of 400MPa by a tablet press to obtain a green sheet, and the temperature was increased at a heating rate of 120°C / min in a nitrogen protective environment. When the temperature reached 500°C, it was maintained at a pressure of 300MPa for 60min, and then the pressure was increased to 4GPa, and then the temperature was increased to 1300°C, and after keeping warm for 10min, it was quenched and unloaded to obtain a welding brazing filler metal.
[0030] Comparative Example 4: A low melting point solder comprises the following components by weight percentage: 9.0% Zn and the balance Sn, and the specific preparation method comprises the following steps: Weigh Sn particles with a purity of 99.99% and Zn particles with a purity of 99.9% according to a certain weight percentage and put them into a quartz tube. Reduce the vacuum degree in the quartz tube to 4×10 -2 Pa, nitrogen was filled in until the pressure reached 0.3MPa, and the welding brazing material was obtained by melting heat treatment at a temperature of 550°C for 60min in a nitrogen protection environment and then cooling.
[0031] Comparative Example 5: A low melting point solder comprises the following components by weight percentage: 9.0% Zn, 3.0% Mn, 2.6% Bi, 0.5% Hf and the balance Sn, and the specific preparation method comprises the following steps: Weigh Sn particles with a purity of 99.99%, Zn particles with a purity of 99.9%, Bi particles, Mn particles, and Hf particles according to a certain weight percentage and put them into a quartz tube. Reduce the vacuum degree in the quartz tube to 4×10 -2Pa, nitrogen was filled in until the pressure reached 0.3MPa, and the welding brazing material was obtained by melting and heat treatment at a temperature of 1500°C for 2h in a nitrogen protection environment and then cooled.
[0032] Test example: The present invention measured the melting temperature, wetting angle and self-corrosion potential of the solder prepared in Examples 1 to 4 and Comparative Examples 1 to 5 under the same experimental conditions. The results are shown in Table 1.
[0033]
[0034] As shown in Table 1, compared with the pure Sn-Zn solder of Comparative Example 4, the melting point of the solder prepared in Examples 1 to 4 of the present invention is further reduced, and the melting temperature range is similar to that of the Sn-Pb solder, which can be well adapted to the parameter setting and debugging of the current traditional soldering process. At the same time, the wetting angles of the solder prepared in Examples 1 to 4 of the present invention are all lower than those in Comparative Examples 1 to 5, which illustrates the importance of the synergistic effect of Hf and Mn in improving the wettability of the solder. In addition, compared with Comparative Examples 1 to 5, the solder prepared in Examples 1 to 4 has a higher self-corrosion potential. In the principle of solder corrosion, the higher the self-corrosion potential, the more difficult it is for electron transfer to occur on its surface in a humid environment, and it is also less likely to be oxidized or corroded. The preparation method of the welding brazing material provided by the present invention first reacts Zn, Mn and Hf with Sn at high temperature to prepare intermediates 1, 2 and 3 respectively, and then sinters the intermediates 1, 2, 3 and Bi particles under high pressure to obtain the welding brazing material. The above steps make the structure of the prepared welding brazing material more compact and further enhance its corrosion resistance. It can be seen from the above that the welding brazing material provided by the present invention has good wettability and corrosion resistance while maintaining the low melting point characteristics, showing excellent comprehensive performance.
[0035] The above-described embodiments provide a detailed description of the technical solutions and beneficial effects of the present invention. It should be understood that the above description is only a specific embodiment of the present invention and is not intended to limit the present invention. Without departing from the spirit and scope of the present invention, the present invention may have various changes and improvements, which fall within the scope of the present invention to be protected.
Claims
1. A method for preparing a low melting point solder, characterized in that: The preparation method comprises the following steps: Sn particles and Zn particles are subjected to a first smelting heat treatment in an inert gas protective environment and then cooled to obtain intermediate 1, Sn particles and Mn particles are subjected to a second smelting heat treatment in an inert gas protective environment and then cooled to obtain intermediate 2, Sn particles and Hf particles are subjected to a third smelting heat treatment in an inert gas protective environment and then cooled to obtain intermediate 3, intermediate 1, intermediate 2, intermediate 3 and Bi particles are mixed by ball milling, and then sintered under high pressure and quenched to release the pressure to obtain the welding brazing material.
2. The method for preparing a low melting point solder according to claim 1, characterized in that: The purity of the Zn particles is 99.9%.
3. The method for preparing a low melting point solder according to claim 1, characterized in that: The purity of the Sn particles is 99.99%.
4. The method for preparing a low melting point solder according to claim 1, characterized in that: The first smelting has a smelting temperature of 450-550° C. and a smelting time of 30-60 min.
5. The method for preparing a low melting point solder according to claim 1, characterized in that: The smelting temperature of the second smelting is 1300-1500° C., and the smelting time is 40-60 min.
6. The method for preparing a low melting point solder according to claim 1, characterized in that: The smelting temperature of the third smelting is 2300-2500° C., and the smelting time is 80-100 min.
7. The method for preparing a low melting point solder according to claim 1, characterized in that: The high pressure sintering temperature is 900-1200°C.
8. The method for preparing a low melting point solder according to claim 1, characterized in that: The pressure of the high pressure sintering is 3~4GPa.
9. The method for preparing a low melting point solder according to claim 1, characterized in that: The solder is measured by weight percentage. Includes the following components: 9.0% Zn particles, 2.5~3.5% Mn particles, 1.8~2.6% Bi particles, 0.01~0.5% Hf particles and the balance Sn particles.
10. A welding brazing filler metal prepared by the method for preparing a low melting point welding brazing filler metal as claimed in any one of claims 1 to 9.
Citation Information
Patent Citations
Nano-enhanced leadless solder and preparation method thereof
CN101653877A
Low-melting-point lead-free solder and preparation method thereof
CN107052613A
Manufacturing method for low-melting-point Sn-Zn-Bi brazing filler metal alloy
CN108465971A
Tin-base active flux for soldering ceramic under coarse vacuum condition
CN1146390A
Preparation method of AgCuTi active brazing filler metal
CN115519277A